PERKEMBANGAN FITRAH RELIGIUSITAS MANUSIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Askur Amin; Rahmad Rinaldi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to understand how school principals can carry out their leadership according to procedures, and try to explain how school principals in carrying out their leadership are able to move teachers, students, and school residents to always improve the quality of education at MTs Al-Ulum Medan. Things that are observed by related researchers; 1) How is the implementation of the principal's leadership in carrying out its function to improve the quality of the school, 2) What is the role of the principal's leadership in dealing with obstacles in carrying out his duties. For this reason, researchers are interested in conducting research on